Political economy of mangrove management in Ajuy, Iloilo and Ibajay, Aklan, Philippines - Fernandez, Pepito R., Jr (Danyag :the UPV journal of humanities and social sciences, 2005)
"This paper explains and analyzes the role of the Philippine government in the use and management of mangrove forests since the 1950s. National institutional frameworks and trends are described, and two case studies are presented to analyze the issues and concerns confronting the management of mangrove forests in the country. The study veers away from apolitical narratives of environmental change and human-mangrove interactions, and explicitly acknowledges the significant influence of political and economic forces in accounting for environmental crisis, as well as the environmental roles of key stakeholders/actors. Using qualitative field research techniques, applied intermittently from 2001-2005, the study reveals that the costs and benefits of mangrove use and access are unequally distributed among various actors and stakeholders, usually favouring groups and individuals connected with the State. Consequently, the environmental alteration or change that is generated affects the economic status quo or livelihood contexts of different actors. The differentiated social and economic impact of environmental change to different actors not only affects their ability to produce wealth for themselves, but also alters actor relationships or the ability of actors to control or resist other actors."